2015
DOI: 10.5539/ass.v11n15p84
|View full text |Cite
|
Sign up to set email alerts
|

Does Classroom Characteristic Truly Stimulate Learning Motivation and Performance? Reporting from Malaysian Undergraduates’ Perception

Abstract: Some researchers find that learning intervention can stimulate learning motivation and performance through classroom characteristic. Ironically, research assessing classroom characteristic that can be used as potential learning intervention have received little attention especially among Malaysian undergraduates. Hence, the aim of this study is to determine the mediation effect of motivation to learn on the relationship between classroom characteristic and students' grade performance. A number of 173 undergrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Kline [34] suggested that a minimum sample size of at least 200 cases was needed to advance to the next step of SEM. Furthermore, according to Abdul-Aziz et al [35], "information obtained from the census is likely to be more valid and reliable." Thus, these samples were considered sufficient for the SEM analysis.…”
Section: Data Collectionmentioning
confidence: 99%
“…Kline [34] suggested that a minimum sample size of at least 200 cases was needed to advance to the next step of SEM. Furthermore, according to Abdul-Aziz et al [35], "information obtained from the census is likely to be more valid and reliable." Thus, these samples were considered sufficient for the SEM analysis.…”
Section: Data Collectionmentioning
confidence: 99%